2023
DOI: 10.3390/nu15051300
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Oral Supplementation with a Highly-Concentrated Docosahexaenoic Acid (DHA) Triglyceride in Patients with Keratoconus: A Randomized Controlled Preliminary Study

Abstract: A prospective, randomized, single-center preliminary study was performed in patients with keratoconus stages I–III (Amsler–Krumeich), who received a high rich docosahexaenoic acid (DHA) (1000 mg/day) supplement for 3 months versus untreated patients. One eye per patient was evaluated. Thirty-four patients were recruited (75% men, mean age 31 years), with 15 randomized to the control group and 19 to the DHA-treated group. Corneal topography variables and plasma biomarkers of oxidative stress and inflammatory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(55 reference statements)
0
4
0
Order By: Relevance
“… Medications that reduce the often-coexisting allergic and ocular symptoms in KC patients. 13 , 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“… Medications that reduce the often-coexisting allergic and ocular symptoms in KC patients. 13 , 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, patients with keratoconus received DHA (1000 mg) supplementation for three months, resulting in higher total antioxidant capacity and better outcomes in the astigmatism axis, asphericity coefficient, and intraocular pressure than the placebo group [ 165 ].…”
Section: Defense Of Cellular Membranes With Lipophilic Antioxidantsmentioning
confidence: 99%
“…DHA functions as a potent antioxidant and plays a crucial role in neural tissues such as the brain and retina [ 18 ]. Multiple clinical studies have demonstrated that oral supplementation of DHA can significantly improve the oxidative stress state in the blood [ 19 ], alleviate age-related ocular diseases [ 20 ], and provide various benefits, including neuroprotection [ 21 ]. Additionally, its potential role in cancer therapy is increasingly gaining attention.…”
Section: Introductionmentioning
confidence: 99%